A comparative study of funnel shape bottlenecks in subway stations. (April 2017) - Sun, Lishan; Luo, Wei; Yao, Liya; Qiu, Shi; Rong, Jian
Highlights: Funnel shape at bottleneck in subway station is proposed. Funnel shape effectively improves the traffic efficiency at bottleneck, especially under large volume. The specific recommended funnel shape angle depends on passenger flow level. he best performance funnel angle is between 46° and 65° under different passenger volume. Abstract: A bottleneck typically denotes a narrowed area that reduces the flow through a channel. Congestion is expected to form at bottlenecks such as escalator and staircase entrances with high rate of passenger flow, which could decrease walking efficiency and passenger comfort. Currently, no special treatment is adopted in most of the conventional bottlenecks in subway stations. This study conducts a series of pedestrian experiments to investigate the effectiveness of adding a funnel shape buffer zone in front of the bottleneck entrance. Different angles of funnel bottleneck are experimented under different pedestrian volumes. By analyzing factors including walking speed, individual passing time, total passing time, and time gap, it is found that funnel shape would overall improve the traffic effectiveness of the bottlenecks, especially when the flow rate is high. The recommendation of setting funnel angle depends on passenger flow level, the optimal of which should be between 46° and 65°. This study provides a rationale for agencies to improve the current pedestrian traffic efficiency at bottlenecks.